Peran Kantor Pengawasan Bea Dan Pelayanan Bea Dan Cukai Tipe Madya Cukai Kudus Dalam Mengawasi Kebijakan Cukai Rokok Terkait UU No. 39 Tahun 2007 - Shynta Pravitasari; Puji Astuti; Sulistyowati . (Journal of Politic and Government Studies, 2015)
AbstractTobacco product industries have been contributing to the development of thecountry in form of excise deposit that reaches 95 percent in state budget of APBN.The existence of cigarette industries in Indonesia become the source of nationalincome from excise that have been assigned on the type of tobacco product which isregulated in the excise laws number 39 year 2007. Cigarettes as goods have positiveand negative impact, it is important to have control in consumption and monitor of itsdistribution. Customs supervision and service office of medium type kudus’ exciseoffice under the general directorate of customs and excise become one part thatreceive the most abundance excise from other customs supervision and service office.Customs supervision and service office has role in controlling and analyzing thecountry acceptance potency because there are still many violation happening aroundthe customs supervision and service office.This research is aimed to understand the kind of effort that can be done bycustoms supervision and service office in controlling the excise wisdoms, role andfunction of customs supervision and service office and the obstacle that may beexperienced by customs supervision and service office in the implementation ofmonitoring of the excise wisdom. Research methods used is descriptive qualitative.The primary data sources were taken from interview, information from document,archives, and other relevant source to this research.Result of the research show that customs supervision and service office medium type of Kudus’ excise has efforts in monitoring and giving service to the service users through the preventive effort in form of administration monitoring and socializing to the service users and societies that involve in the cigarette industries. Repressive effort is one way to save the country disadvantage and decrease the excise violation. The repressive effort is being done by the physical monitoring and examination to the companies, regular market checking, and treating the violation with criminal and administration sanctions.The suggested recommendation is to increase the monitoring ability within the five working areas of customs supervision and service office of medium type Kudus’ excise by optimizing more performance of customs supervision and service office of medium type Kudus’ excise workers cooperate with local government and give the appeal to society about the danger it may cause because of violation in the cigarette production activities.Keywords:Role of Customs Supervision and Service Office of Medium Type Kudus’ Excise, Wisdom of Cigarettes Excise